Assessment of nickel release from stainless steel crowns. - Nahid Ramazani; Rahil Ahmadi; Mansure Darijani (Tehran University of Medical Sciences, 2014)
Adverse effects of dental materials, especially metals, have been an important issue in recent decades.The purpose of this study was to determine the amount of nickel released from stainless steel crowns in artificial saliva.In this in-vitro study, 270 stainless steel crowns were divided into five groups, each with nine subgroups. Each group (I to V) was comprised of four, five, six, seven and eight crowns, respectively. Each subgroup was placed in a polyethylene jar containing artificial saliva and held in an incubator at 37°C for four weeks. The amount of released nickel was determined on days 1, 7, 14, 21 and 28, using an atomic absorption spectrophotometer. Wilcoxon Signed-Rank and Kruskal-Wallis with Dunn's post hoc tests (SPSS software, v. 18) were used for statistical analysis at a significance level of 0.05.The mean level of nickel on day 1 was more than that of day 7; this difference was statistically significant for all groups (P < 0.05), except for group II (P = 0.086). Also, the mean difference of released nickel between the groups was significant on day 1 (P = 0.006) and was insignificant on day 7 (P = 0.620). The nickel levels were zero on days 14, 21, and 28.The amount of nickel was below the toxic level and did not exceed the dietary intake.